2016
DOI: 10.4038/cmj.v60i4.8223
|View full text |Cite
|
Sign up to set email alerts
|

Aortic annular measurements in fresh post-mortem hearts: a study in Sri Lankans

Abstract: The basal aortic root measurements were determined in 320 fresh, autopsied, normal, adult, Sri Lankan hearts collected from the Judicial Medical Office, National Hospital of Sri Lanka. The correlation between the measurements and demographic data of the individual was calculated. The mean aortic root circumference at the basal ring was 64.7 mm ± 7SD (males 66.0mm ± 6.4SD, females 58.0mm ± 6.1SD) and calculated aortic annular diameter was 20.60mm ± 2.2SD (males 21.02mm ± 2.0SD, females 18.47mm ± 1.9SD). Mean ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…However, the data in the previous studies showed some different results compared with this study. Before formalin fixation, the average heart valve circumference in this study was slightly higher than in almost all the previous studies [5][6][7][8][9][10][11][12][13][14] , but lower than that reported by Tei et al 15 and coincided with those reported by Jatene et al 8 and Alison et al 23 Nevertheless, the average heart valve circumference after formalin fixation was slightly lower or similar to the above-mentioned studies. Why there was such a difference between our study and previous studies might be explained by the different socio-economic status and population groups from which the hearts were obtained as well as by the factors affecting formalin fixation, as mentioned above.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, the data in the previous studies showed some different results compared with this study. Before formalin fixation, the average heart valve circumference in this study was slightly higher than in almost all the previous studies [5][6][7][8][9][10][11][12][13][14] , but lower than that reported by Tei et al 15 and coincided with those reported by Jatene et al 8 and Alison et al 23 Nevertheless, the average heart valve circumference after formalin fixation was slightly lower or similar to the above-mentioned studies. Why there was such a difference between our study and previous studies might be explained by the different socio-economic status and population groups from which the hearts were obtained as well as by the factors affecting formalin fixation, as mentioned above.…”
Section: Discussionsupporting
confidence: 87%
“…Currently, there is no standard method to measure heart valve circumference. With reference to previous studies [5][6][7][8]10,12,13 , the thread and ruler technique was the most popular practice to evaluate the heart valve circumference. Because none of the above-mentioned studies provided data on direct measurement, no comparisons can be made.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this study was done on freshly autopsied adult human hearts, it excludes the error due to fixation [18]. It is designed to gather anthropometric cardiac measurements in a sub set of Sri Lankan population.…”
Section: Discussionmentioning
confidence: 99%
“…This type of anthropometric data are a prerequisite for the accurate interpretation of echocardiography, ante-mortem and post-mortem cardiac MRI and CT [10][11][12], surgical reconstruction and repair of the heart and valves [18,19] and interpretation of cardiac measurements in pathological and medico-legal autopsies. There appears to be a geographical/racial variation on the norms of measurements for the heart and it was proven in most of the studies done in other countries [20][21][22] as well as in Sri Lanka [18,19]. Data on normal cardiac anthropometric measurements for the Sri Lankan population are scarce and scanty.…”
Section: Discussionmentioning
confidence: 99%